Pengaruh Servant leadership Kyai dan Motivasi Belajar terhadap Minat Santri Melanjutkan Pendidikan Tinggi dengan Dukungan Sosial sebagai Moderasi - Faizah, Nur; Abidin, Munirul; Fitriani (Transformation of Islamic Management and Education, 2025)
The high number of students who do not continue their higher education is a problem for Islamic boarding schools, especially in improving the quality of human resources. One of the reasons is the lack of social support, lack of motivation to learn, and lack of leadership oriented towards student development. This study aims to analyze the influence of social support and servant leadership on students' learning motivation and its impact on their interest in continuing higher education. This study uses a quantitative approach with the SmartPLS-based Structural Equation Modeling (SEM) method. The data was collected through a questionnaire distributed to students at one of the Salafi Islamic boarding schools. The results of the study show that social support has a positive and significant effect on learning motivation and interest in continuing higher education. Servant leadership also has a positive and significant influence on students' motivation to learn. However, learning motivation does not significantly affect students' interest in pursuing higher education, which indicates that there are other factors that are more dominant in influencing students' decisions. In addition, the interaction between social support and servant leadership on learning motivation did not show a significant effect. The implications of this study emphasize the importance of increasing social support and the implementation  of servant leadership in pesantren in order to build an environment conducive to increasing students' motivation to learn and interest in continuing their education to a higher level.